Wirtschafts- und Finanzpolitik als Schlüsselbereiche europäischer Einigung - Schönhärl, Korinna; Leucht, Brigitte (Europäische Einigung zwischen Anspruch und Wirklichkeit. Eine historische Bestandsaufnahme)
Im Gespräch loten Brigitte Leucht und Korinna Schönhärl aus, welche Rolle wirtschafts- und finanzpolitische Überlegungen und Faktoren für den europäischen Einigungsprozess gespielt haben und immer noch spielen.
Keywords: Wirtschaftsgeschichte; Europäische Geschichte; Europäische Einigung; Staatsverschuldung; Moderne griechische Geschichte

Histories of Tax Evasion, Avoidance and Resistance - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea
Tax evasion, tax avoidance and tax resistance are widespread phenomena in political, economic, social and fiscal history from antiquity through medieval, early modern and modern times. Histories of Tax Evasion, Avoidance and Resistance shows how different groups and individuals around the globe have succeeded or failed in not paying their due taxes, whether in kind or in cash, on their properties or on their crops. It analyses how, throughout history, wealthy and poor taxpayers have tried to avoid or reduce their tax burden by negotiating with tax authorities, through practices of legal or illegal tax evasion, by filing lawsuits, seeking armed resistance or by migration, and how state authorities have dealt with such acts of claim making, defiance, open resistance or elusion. It fills an important research gap in tax history, addressing questions of tax morale and fairness, and how social and political inequality was negotiated through taxation. It gives rich insights into the development of citizen-state relationships throughout the course of history. The book comprises case studies from Ancient Athens, Roman Egypt, Medieval Europe, Early Modern Mexico, the Ottoman Empire, Nigeria under British colonial rule, the United Kingdom of the early 20th century, Greece during the Second World War, as well as West Germany, Switzerland, Sweden and the United States in the 20th century, including transnational entanglements in the world of late-modern offshore finance and taxation. The authors are experts in fiscal, economic, financial, legal, social and/or cultural history. The book is intended for students, researchers and scholars of economic and financial history, social and world history and political economy. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Share Alike 4.0 license.
Keywords: Tax History; Financial History

The Ability and Intention of Not Paying Taxes in History. Some Introductory Observations - Schönhärl, Korinna; Hürlimann, Gisela; Rohde, Dorothea (Histories of Tax Evasion, Avoidance and Resistance)
Jean Bodin's list on how the absolutist monarchical state could raise its revenue ranked taxation only in seventh place. From a modern legal perspective, taxes are compulsory transfers of resources that households and enterprises pay to one or several government bodies without receiving an individual, specific benefit in return. Historians have dealt with not paying taxes in various contexts, such as analysing tax resistance and tax resistance movements in history. Tax law is best understood as an outcome of long-term, often conflictual, negotiations and as an expression of specific political mentalities and ideologies. As a consequence, tax law and sometimes even the tax juridical system have a strongly politicised character. Loopholes in tax legislation that enable or facilitate avoidance or evasion can thus be regarded as a result of the interest-driven politics of parliamentary majorities, as the success of concerted lobby pressure.

How to Create a Taxpaying Spirit. A Transnational Examination of an US American and a Western German Tax Education Film in and after World War II - Schönhärl, Korinna (Histories of Tax Evasion, Avoidance and Resistance)
As a case study, this chapter examines two tax education films that were produced 11 years apart in the USA and Western Germany during and after World War II: “The New Spirit” and “Putzke wants to know”. In contrast to America's most popular cartoon character 11 years earlier, Erwin Putzke is in a terrible mood at the beginning of the short film “Putzke wants to know”. The family father and electrician with a workshop of his own is annoyed and upset by the duty of filling in his tax return, grumbling at his wife and daughter and even at their budgie. The film's tax morale message is conveyed to its audience against the backdrop of a sober post-war reality characterised by allied occupation and the Allies' say in West German tax policies during a period of laborious economic build-up after a lost war.

Tax Education After WWII: How Spain, the USA, and West Germany Tried to Make Their Citizens Pay Honestly - Schönhärl, Korinna; Düll, Nasrin; Ramírez Lugo , Nadya Melina (Tax Evasion and Tax Havens since the Nineteenth Century)
State education in honest tax payment can be understood as a facet of training in citizenship, i.e. as an attempt by the modern state to standardize the behavior of its citizens and to prevent deviations. Based on this Foucauldian understanding, this exploratory article examines tax education in the United States, Spain, and West Germany from the mid-1940s to the late 1980s. During this period, the USA asserted itself as the champion of tax education and Spain consistently tried to emulate this example, albeit with more modest means and different semantic strategies from as early as the 1960s, when it was still under a autoritarian regime. The FRG, however, completely discontinued its few early attempts at tax education from the mid-1950s onwards. Even during the economic crises and tax scandals of the 1970s, there was no relaunch of the programs. The article locates the reasons for this highly uneven development in the different ideal images of the citizen in the three states.

Editorial - Schönhärl, Korinna; Schotters, Frederike; Thiemeyer, Guido (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Ver- gangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischen- menschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuch en Gelddis- kurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Internationale Finanzkontrollen: Griechenland unter internationaler Kuratel im 19. und 21. Jahrhundert - Schönhärl, Korinna (Schulden machen: Praktiken der Staatsverschuldung im langen 20. Jahrhundert)
Ob als Effekt staatlicher Hilfspakete, als kontroverses Thema des EU-Haushalts oder als mögliche Ursache der rasant steigenden Inflation – in einer Welt im Krisenmodus ist das Problem der Staatsverschuldung aktuell wie selten zuvor. Wie und von wem aber werden Staatsschulden tatsächlich »gemacht«? Und wie stellt sich dies in der historischen Perspektive dar? Die Essays dieses Bandes machen das abstrakte Phänomen der öffentlichen Verschuldung und die verborgenen Prozesse hinter den Schuldenquoten zugänglich. Prägende Praktiken der Staatsverschuldung verdeutlichen die Beiträge anhand von fünf Kategorien: den beteiligten Akteuren, den konkreten Artefakten, den politischen Debatten, den globalen Relationen sowie der Zeitlichkeit der Verschuldung der öffentlichen Haushalte.
Keywords: Financial History; Public Debt; Economic History

Reden über Geld (Werkstatt Geschichte)
»Über Geld spricht man nicht.« Diese Benimmregel erweist sich beim Blick in die Vergangenheit als Illusion. Keineswegs war Geld grundsätzlich ein Tabuthema zwischenmenschlicher Kommunikation. Ganz im Gegenteil: Mit dem Reden über Geld wird dieses mit Bedeutung aufgeladen. Die Autor*innen dieses Themenheftes untersuchen Gelddiskurse und die Zuschreibungen von Bedeutung an Geld in der internationalen Geschichte.
Keywords: Financial History; Discourse Analysis; History of Money

Tax Morale and the Church: How Catholic Clergies Adapted Norms of Paying Taxes to Secular Institutions (1940s–1950s) - Schönhärl, Korinna (Reassessing the Moral Economy Religion and Economic Ethics from Ancient Greece to the 20th Century)
Paying taxes is a field of economic activity that has always been highly morally charged: the question of who pays how much or can avoid or evade the prescribed payments is always closely related to debate about a fair societal distribution of burdens. In the process of moralisation, therefore, faith communities such as the Catholic Church also repeatedly seized the floor to propagate certain norms. The article examines the contributions of theologians from Spain, the USA and West Germany in the 1940s and 1950s. It concludes that the norms of taxation they propagated differed greatly depending on the institutional and economic frameworks within which they operated. The analysis proves taxation to be a field of economic action and societal dispute where economics and morality are indissolubly interconnected.
Keywords: Tax history; religious history: financial history; catholic church; history of economic thought

Review on: Christos Tsakas: Post-war Greco-German Relations, 1953-1981. Economic Development, Business Interests and European Integration, Basingstoke 2022. - Schönhärl, Korinna (Sehepunkte)

Review on: Daniel Benedikt Stienen: Verkauftes Vaterland - Schönhärl, Korinna (Sehepunkte)

Review on: Sven Steinmo: Willing to Pay? A Reasonable Choice Approach - Schönhärl, Korinna (HSozKult)

"Ein Steuerzahler!" Tax education in der frühen Bundesrepublik - Schönhärl, Korinna (Ökonomie und Moral im langen 20. Jahrhundert. Eine Anthologie)

Reconciliation in Resignation: The 2015 Greek Referendum on the Lenders’ Conditions - Schönhärl, Korinna (Journal of European Integration History)

Germany - Schönhärl, Korinna; Osterloh-Konrad, Christine (History and taxation. The dialectical relationship between taxation and the political balance of power: 2021 EATLP Congress Antwerp, 3-4 June 2021)

Review on: Gerold Ambrosius/ Christian Henrich-Franke: Diversität, Transformation, Kontinuität. Europa 1800–1870 - Schönhärl, Korinna (VSGW)

Steuerzahlverhalten quantifizieren - Schönhärl, Korinna (Jahrbuch für Wirtschaftsgeschichte / Economic History Yearbook)
From the 1880s scientists developed methods to measure (dishonest) tax payment behaviour. The first part of this article provides an overview of these methods and their development. The second part enquires into the function of measuring methods in the societal discourse about (honest) tax payments. The tax morale research of Günter Schmölders, carried out in the 1950s and 1960s, is then examined as a case study. The focus of interest is on the political advice that Schmölders gave, as based on his empirical results, and on the ideal image of the citizen and society which underlay the scientific method.
Keywords: Economics and Econometrics; History

Einleitung: Staatsfinanzen und Konflikt - Schönhärl, Korinna; Spoerer, Mark (Jahrbuch für Wirtschaftsgeschichte / Economic History Yearbook)
The following issue arose from a section at the Congress for Economic and Social History in Regensburg in March 2019 and focuses on fiscal conflicts in Europe from the early modern period until today. Distributive fiscal conflicts are seen here as a probe into the past which can increase our understanding of historical social structures. Fiscal history is analysed as a central arena of the modern state. The introduction provides an overview of current research into fiscal history in Germany and of the contributions presented in this focus issue.
Keywords: Economics and Econometrics; History

Jahrbuch für Wirtschaftsgeschichte/Economic History Yearbook- Schwerpunktheft: Staatsfinanzen und Konflikt

'Unfortunately we are bankrupt': The Greek Bankruptcy Crisis of 1893 and its Remembrance in the World Economic Crisis 2010-11 - Schönhärl, Korinna (Remembering and Learning from Financial Crises)

Why does a prestigious emission house emit a loan for a peripheral state? The house of Rothschild and the Greek guaranteed loan of 1833 - Schönhärl, Korinna (Business History)
How did bankers make their investment decisions, for example to issue a state loan for a peripheral country? This in-depth case study investigates the question of the Greek loan of 1833, issued by Rothschilds. The main interest is to reconstruct James de Rothschild’s risk perception and decision making process, expressed in the argumentation vis-à-vis his family. The significance of the guarantee of the protecting powers, which was without precedent, is considered by James as well as the competitive situation on the bond market, the relationship of the Rothschilds with leading politicians of the time, and the special significance of Greece in the period of intensive European philhellenism. The paper argues that in-depth studies of bankers’ risk perception are necessary to illuminate the complexity of their decision-making.
Keywords: History; Business; Management and Accounting (miscellaneous); Business and International Management

Finanzielle Netze. Die bayerisch–französische Familienbank von Eichthal und ihre Investitionspläne in Griechenland in den 1830er Jahren/ Οικονομικά δίκτυα. Η βαυαρογαλλική οικογενειακή τράπεζα των Άιχταλ και τα επενδυτικά σχέδιά της στην Ελλάδα κατά τη δεκαετία του 1830 - Schönhärl, Korinna
Als Griechenland 1830 seine Unabhängigkeit erlangte, war das Land wirtschaftlich wenig entwickelt und von der Industrialisierung noch kaum berührt. Kredite für die Gründung oder den Ausbau von Unternehmen waren auf Grund des Kapitalmangels entweder unmöglich oder extrem teuer – ein für die wirtschaftliche Entwicklung ernst zu nehmendes Hemmnis. Das Land brauchte zur wirtschaftlichen Entwicklung also Investitionen aus dem Ausland. Jedoch hielten sich die europäischen Banken und Anleger mit solchen Investitionen vor den 1870er Jahren zurück. Warum diese Scheu der Kapitalanleger vor Griechenland, obwohl sie anderswo keineswegs vor risikoreichen Investitionen zurückschreckten, wenn nur entsprechend hohe Erträge lockten? Dieser Frage möchte der Beitrag anhand eines Beispiels nachgehen: der bayerisch-französischen Bankiersfamilie von Eichthal, die in den 1830er Jahren enge Geschäftsbeziehungen nach Griechenland aufbaute und zeitweilig sehr interessiert an Investitionen war – bevor das Bankhaus sich von diesen Plänen schließlich unverrichteter Dinge wieder abwandte. Das kulturelle Interesse an Griechenland überdauerte dagegen bis in die 1880er Jahre. Die Eichthals eignen sich hervorragend, um paradigmatisch zu untersuchen, auf welcher Grundlage und wie europäische Bankiers ihre Investitionsentscheidungen für oder gegen Griechenland trafen.

European Investment in Greece in the Nineteenth Century - Schönhärl, Korinna

„Wie tief der kern dieses Volkes dem antiken wesen verwandt ist“ „Cultural Brokers“ und ihre Strategien zur Vermittlung des Unbekannten - Schönhärl, Korinna (Historische Zeitschrift)
Der vorliegende Aufsatz fragt nach Strategien kultureller Vermittler, den bei der Erstbegegnung mit einer fremden Kultur eintretenden Schock zu verarbeiten und die kulturellen Differenzen neu zu semantisieren und sinnhaft zu deuten. Er greift drei geografisch und chronologisch weit auseinanderliegende Fallbeispiele von kulturellen Vermittlern auf, die vor dem Hintergrund ihres umfassenden antiken Bildungswissens versuchten, die Fremde als „lebende Antike“ zu interpretieren: Missionare in Neuspanien im 16. und 17. Jahrhundert, einen Griechenlandreisenden der 1830er und einen Japanreisenden der 1930er Jahre. Der analysierte Vermittlungsprozess wird als „doppelte Allelopoiese“ beschrieben: die brokers stilisierten einerseits die Antike als zwar weit zurückliegenden, aber essentiellen Teil ihrer eigenen kulturellen Identität; sie parallelisierten andererseits die fremde Lebenswelt, mit der sie konfrontiert wurden, mit eben dieser Antike; in einem (nur analytisch zu isolierenden) dritten Schritt konnten sie so Parallelen zwischen der Fremde und dem Eigenen hervorheben und wechselseitige kulturelle Aneignungen (Transformationen) einleiten und rechtfertigen. Der Artikel schlägt eine weitere Ausarbeitung der „doppelten Allelopoiese“ als analytisches Instrument für die Erforschung der cultural brokers vor.
Keywords: History

Das griechische Referendum von 2015 über die Konditionen der Euro-Gruppe - Schönhärl, Korinna (Südosteuropa Mitteilungen)

Die Kosten der Rettung Europas: Schulden- und Steuerkulturen in historischer Perspektive - Schönhärl, Korinna; Buggeln, Marc

Review: Günther Schulz, Mark Spoerer (Ed.): Integration und Desintegration Europas: Wirtschafts- und sozialhistorische Beiträge (VSWG Beiheft 244), Stuttgart 2019 - Schönhärl, Korinna (Journal of European Integration History)

Steuermoral in Westdeutschland nach dem Zweiten Weltkrieg. Eine diskursanalytische Rekonstruktion - Schönhärl, Korinna (Leviathan)
Die Klage über mangelnde Steuermoral ist in der aktuellen Medienberichterstattung omnipräsent, aber sie ist nicht neu: Bereits kurz nach dem Zweiten Weltkrieg wurde bemängelt, die Deutschen in den westlichen Besatzungszonen hinterzögen ihre Steuern. Verfiel die westdeutsche Steuermoral schon damals? Wie veränderte sie sich im Zeitraum zwischen 1945 und 1953? Nach einem kurzen Überblick über die Geschichte der interdisziplinären Steuermoralforschung und einigen methodischen Überlegungen, wie Historiker*innen die Entwicklung der Steuermoral qualitativ untersuchen können, wird im vorliegenden Aufsatz der Diskurs um das Steuerzahlen in der Nachkriegszeit analysiert. Durch die Analyse von Zeitungsberichten und Parlamentsdebatten werden drei unterschiedliche, konkurrierende Narrative identifiziert, die geeignet waren, ganz verschiedene »policy windows« zu öffnen. Die historische Untersuchung zeigt, dass Narrative über das (ehrliche) Steuerzahlen immer mit bestimmten politischen Interessen verknüpft sind - und dass sie deshalb auch im aktuellen Diskurs über das (ehrliche) Steuerzahlen sorgfältig analysiert werden sollten.
Keywords: Political Science and International Relations; Linguistics and Language; Sociology and Political Science; Language and Linguistics

Socially Responsible Investment in 19th Century Greece: A Case Study of a Swiss Banker - Schönhärl, Korinna (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Altruistically motivated investment has become the subject of economic, psychological and sociological research in recent years. The long tradition of ethical considerations concerning investment behavior has often been mentioned by historians but rarely investigated. This paper presents a case study of the 19th century philhellene banker Jean-Gabriel Eynard, who was philanthropically active in Greece, but also invested part of his capital on the emerging Greek market. Drawing on the methodological approach of the “sociology of morality”, this article examines how Eynard invested in Greece, which norms and values concerning investment behavior he articulated and how far they were comparable with the norms and values of today’s Socially Responsible Investment. What emerges is that the practices and the norms of Socially Responsible and Ethical Investment then and now are remarkably similar, while the “moral background” (G. Abend) has changed considerably in some, but not all points.
Keywords: Economics; Econometrics and Finance (miscellaneous); Sociology and Political Science; History; Cultural Studies

„Der Imperativ des Nassauerns, Durchmogelns und Absahnens“: Debatten um Steuermoral in der BRD Anfang der 1980er Jahren - Schönhärl, Korinna (Geschichte in Wissenschaft und Unterricht)

Geld zurück! Internationale Finanzkontrolle in Griechenland im 19. Jahrhundert und in der Gegenwart - Schönhärl, Korinna (Grenzüberschreitende institutionalisierte Zusammenarbeit von der Antike bis zur Gegenwart)

Die Steuermoral weltweit. Eine Artikelserie in der Frankfurter Allgemeinen Zeitung in den Jahren 1963/64 - Schönhärl, Korinna (Moderner Kapitalismus. Wirtschafts- und unternehmenshistorische Beiträge)

Emotions in decision-making processes: The family bank Eichthal and its investment decisions for Greece in the 19th century - Schönhärl, Korinna (Entreprises et histoire)

Why Invest in Greece? Gerson von Bleichröder and the Greek Loan of 1889 - Schönhärl, Korinna (German-Greek Yearbook of Political Economy)

Review: Bormann, Patrick; Scholtyseck, Joachim: Der Bank- und Börsenplatz Essen. Von den Anfängen bis zur Gegenwart, München 2018 - Schönhärl, Korinna (H-Soz Kult)

Review: Nelson, Stephen C., The currency of confidence: how economic beliefs shape the IMF’s relationship with its borrowers, Ithaca, NY and London 2017 - Schönhärl, Korinna (Economic History Review)

Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century

Finanziers in Sehnsuchtsräumen. Europäische Banken und Griechenland im 19. Jahrhundert - Schönhärl, Korinna
Wie treffen Bankiers ihre Entscheidungen? Wie identifizieren und managen sie Risiken? Wie funktioniert der Aufbau von Vertrauen im Bankgewerbe? Die Studie untersucht diese Fragen am Fallbeispiel Griechenlands und zeichnet die Integration dieses peripheren Finanzmarktes in den europäischen zwischen 1820 und 1914 nach. Ausgehend von methodischen Anregungen der Behavioural Finance analysiert sie in neun Fallbeispielen (u.a. Auslandsanleihen, die Gründung der Nationalbank, die Trockenlegung von Sumpfgebieten, der Kanal von Korinth, die internationale Finanzkommission, der Handel) die Risikoperzeption und das Investitionsverhalten britischer, französischer, deutscher und schweizerischer Bankiers. Griechenland im Zeitalter des Philhellenismus erscheint dabei als »Sehnsuchtsraum«, wo jeder Investor vor dem Hintergrund bestimmter, polarisierender Stereotype seine Entscheidungen zu füllen hatte, die oft auf die Antike rekurrierten und stark emotional aufgeladen waren. Durch die Engführung von Kultur-, politischer und Finanzgeschichte rückt die Vielschichtigkeit der Risikoperzeption in den Blick, bei der Netzwerke oder der Einfluss der Politik ebenso Entscheidungen bedingen konnten wie der unbedingte Glaube an wissenschaftliche Expertise oder nationale Selbstüberschätzung. Die Studie gibt Auskunft darüber, wie sich die Risikoeinschätzung und das Risikomanagement von Bankiers im Laufe des 19. Jahrhunderts veränderten

The European Perception of Greece as an Investment Market in the Nineteenth Century - Schönhärl, Korinna (Business Cycles in Economic Thought: A history)
Introduction It is not only Greece’s present financial problems and its trouble to attract foreign investors that encourage the research of the past of this chapter of financial history. In addition, Greece’s past provides an inspiring case study that illuminates bankers’ investment decisions in crisis-ridden markets. After its Struggle for Independence from 1821 onward, Greece became a nation state in its own right in the year 1830, independent from the Ottoman Empire (Zelepos, 2014, 37-53). In the preceding Ottoman time there was no foreign investment in the area at all. However by the brink of the Balkan wars in 1911-1912, Greece was perceived by foreign investors as a well-established investment market for state loans as well as private investment in various sectors of trade and industry. How was this process driven forward in spite of the three financial breakdowns that occurred during this period (1825, 1843 and 1893)? How were the ups and downs of the Greek economy perceived and interpreted from abroad? The aim of this chapter is to show interconnections between financial, political and cultural history concerning the development of foreign investment in Greece.

Behavioural Finance as a Methodological Approach for Historians? A Field Report Concerning the Construction of the Canal of Corinth in Nineteenth-Century Greece - Schönhärl, Korinna (Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century)
Historians investigating the risk perception of bankers and the decision-making processes in banks could consider the behavioural finance approach to investigate their sources. In this chapter, this is illustrated using a case study concerning the financing of the construction of a maritime canal at Corinth (1882–1893). It can be shown that the risk perception of the French bank Comptoir d’Escompte can be analysed following the model of Joseph A. Litterer. The bankers’ investment decision was influenced by two biases described by behavioural finance as ‘belief in experts’ and ‘overconfidence’. The analysis of the way these biases came about and worked allows banking, political and cultural history to be combined in a coherent narrative

Introduction - Schönhärl, Korinna (Decision Taking, Confidence and Risk Management in Banks from Early Modernity to the 20th Century)

Bis repetita non placent. Griechische Finanzkontrolle im 19. Jahrhundert und in der Gegenwart im Vergleich - Schönhärl, Korinna

Orientfaszination im George-Kreis - Schönhärl, Korinna; Mangold-Will, Sabine (Kreis aus Kreisen. Der George-Kreis im Kontext deutscher und europäischer Gemeinschaftsbildung)

Review: Schwarz, Steffen L.: Despoten – Barbaren – Wirtschaftspartner. Die Allgemeine Zeitung und der Diskurs über das Osmanische Reich 1821-1840, Köln Weimar Wien 2016 - Schönhärl, Korinna (H-Soz Kult)

„Leider sind wir bankrott“. Zahlungsausfälle in der Geschichte Griechenlands im 19. und 20. Jahrhundert - Schönhärl, Korinna (Die Krise in Griechenland. Ursprünge, Verlauf, Folgen)

Die Internationale Finanzkommission für Griechenland von 1898 oder: Stereotypen leben lange - Schönhärl, Korinna

Review: Dahlmanns, Karsten: Das verfluchte Amerika. Stefan Georges Bildnis von Unternehmertum, Markt und Freiheit, Würzburg 2015 - Schönhärl, Korinna (Germanistik)

Vertrauensarbeit nach dem Bankrott: Die Internationale Finanzkommission für Griechenland zwischen 1898 und 1914 - Schönhärl, Korinna (Finanzpolitik und Schuldenkrisen 16.-20. Jahrhundert)

Review: Hervé Le Bret: Les frères d'Eichthal. Le saint-simonien et le financier au XIX siècle, Paris 2012 - Schönhärl, Korinna (Francia Recensio)

Review: Hubert Bonin: French Banks and the Greek "Niche Market" mid-1880s-1950s, Geneva 2013 - Schönhärl, Korinna (Financial History Review)

Fighting the Financial Crisis in Greece: The Privileged Company to Protect Production and Trade in Currants (1905) as International Bank Cooperation - Schönhärl, Korinna (The Historical Review/La Revue Historique)
The global economic crisis in the 1890s affected the economy of Greece severely, and in 1893 the Greek State had to stop servicing its foreign debt. Part of the problem was the lack of diversity of Greek agricultural production, which was focused on raisins and currants (especially flavourful raisins, grown exclusively in the area around Corinth) for export. The collapse of market prices for this good seriously affected the Greek treasury and society in the growing regions. The Greek government responded by trying to withhold part of the harvest in fertile years to stabilise world market prices. Plans to organise a monopoly company for the currant trade necessitated high sums of capital from abroad. This article investigates the question of how foreign bankers in London (Hambro & Son, Emile Erlanger) and Paris (Banque de l’Union Parisienne) could be convinced to participate in the project. Which factors allowed foreign bankers to trust in the Greek national economy despite its poor reputation? What factors influenced their risk management? The focus is on the role of Greek brokers in persuading the foreigners to invest in Greece, especially the role played by Ioannis Pesmazoglou, the director of the young and innovative Bank of Athens.
Keywords: History

The Economies of Urban Diversity. The Ruhr Area and Istanbul
The Economics of Urban Diversity explores ethnic and religious minorities in urban economies. In this exciting work, the contributors develop an integrative approach to urban diversity and economy by employing concepts from different studies and linking historical and contemporary analyses of economic, societal, demographic, and cultural development. Contributors from a variety of disciplines geography, economics, history, sociology, anthropology, and planning make for a transdisciplinary analysis of past and present migration-related economic and social issues, which helps to better understand the situation of ethnic and religious minorities in metropolitan areas today.

Warum Geld für Hellas? Die Verschuldung Griechenlands in den 1880er Jahren - Schönhärl, Korinna (Bankenhistorisches Archiv)

Themenheft: Die Börse als Ort von Ressourcenkonflikten im 19. und 20. Jahrhundert (Bankhistorisches Archiv)

The Economies of Urban Diversity: An Introduction - Reuschke, Darja; Salzbrunn, Monika; Schönhärl, Korinna (The Economies of Urban Diversity)
As European Capitals of Culture in 2010 and metropolitan areas of immigration and transmigration, both Istanbul and the Ruhr Area (Essen was designated as European Capital of Culture on behalf of the Ruhr Area) share a complex cultural and social history. Strong human, political, and economic ties have long linked the European Capital of Culture of Turkey to Germany’s main immigration region, which is about to become a new cultural center thanks to the recognition of its industrial heritage by UNESCO (Zeche Zollverein in Essen).1 Even though the cultural history of each region is different, a crisscross reading of ‘parallel lives’ between the two countries helps to understand better the use and the potential of urban diversity over time

„Urbanität“ in Zeiten der Krise: Der Basler Arbeitsrappen - Schönhärl, Korinna (Neue Städte für einen neuen Staat. Die städtebauliche Erfindung des modernen Israel und der Wiederaufbau in der BRD. Eine Annäherung)

Review: Wiczlinski, Verena von: Im Zeichen der Weltwirtschaft. Das Frankfurter Privatbankhaus Gebr. Bethmann in der Zeit des deutschen Kaiserreichs 1870–1914. (Schriftenreihe des Instituts für Bankhistorische Forschung e. V., Bd. 23.), Stuttgart 2011 - Schönhärl, Korinna (HZ)

Review: Schulz, Oliver: Ein Sieg der zivilisierten Welt? Die Intervention der europäischen Großmächte im griechischen Unabhängigkeitskrieg (1826–1832). Münster 2011 - Schönhärl, Korinna (H-Soz-u-Kult)

Review: James, Harold und Müller, Martin L. (Ed.): Georg Solmssen. Ein deutscher Bankier. Briefe aus einem halben Jahrhundert 1900-1956, München 2012 - Schönhärl, Korinna (HZ)

Der Wiener Kongress als „Kinderstube“ des Philhellenismus: das Beispiel des Bankiers Jean-Gabriel Eynard - Schönhärl, Korinna; Kerschbaumer, Florian (Forum Vormärz-Forschung)

Der Georgeaner Kurt Singer in Japan: „Die aber wie der Meister sind, die gehen, und Schönheit wird und Sinn wohin sie sehen.“ - Schönhärl, Korinna; Schefold, Bertram (Studien zur Entwicklung der ökonomischen Theorie XXVII)

Die griechische Staatsverschuldung in der zweiten Hälfte des 19. Jahrhunderts - Schönhärl, Korinna; Psalidopoulos, Michalis (Vom Wohl und Wehe der Staatsverschuldung. Erscheinungsformen und Sichtweisen von der Antike bis zur Gegenwart)

Strukturelle Wirtschafts- und Finanzprobleme Griechenlands im 19. Jahrhundert - Schönhärl, Korinna (Hellenika. Jahrbuch für griechische Kultur und deutsch-griechische Beziehungen)

Edgar Salins Wiederentdeckung von Friedrich List: Die Legitimation der „Anschaulichen Theorie“ durch die Suche nach Vordenkern - Schönhärl, Korinna (Transfer und Wiederaneignung von Wissen)

Review: Wagner-Hasel, Beate: Die Arbeit des Gelehrten. Der Nationalökonom Karl Bücher (1847-1930). Frankfurt am Main 2011 - Schönhärl, Korinna (H-Soz-u-Kult)

Review: Oelmann, Ute und Raulff, Ulrich, Frauen um Stefan George (Castrum Peregrini Neue Folge Bd. 3), Göttingen 2010 - Schönhärl, Korinna (NPL)

Wie eine Blume die erfroren ist“. Edith Landmann als Jüngerin Stefan Georges - Schönhärl, Korinna (Stefan George: Dichtung - Ethos - Staat. Denkbilder für ein geheimes europäisches Deutschland)

Review: Lingelbach, Gabriele: Spenden und Sammeln. Der westdeutsche Spendenmarkt bis in die 1980er Jahre. Göttingen 2009 - Schönhärl, Korinna (H-Soz-u-Kult)

Review: Adam, Thomas; Lässig, Simone; Lingelbach, Gabriele (Hrsg.): Stifter, Spender und Mäzene. USA und Deutschland im historischen Vergleich. Stuttgart 2009 - Schönhärl, Korinna (H-Soz-u-Kult)

Das Ideal des schönen Lebens und die Wirklichkeit der Weimarer Republik. Vorstellungen von Staat und Gemeinschaft im George-Kreis
Der in den Zwanziger Jahren erregt geführte Krisendiskurs erklärte die Gegenwartsprobleme der Weimarer Republik zum Höhepunkt einer Krise der Moderne insgesamt. Aus dieser Perspektive heraus erschien es sinnlos, die Verhältnisse zu reformieren, ein radikaler Neuentwurf war nötig, um die Strukturdefekte der Moderne zu überwinden. Diese Lage bildet den historischen Hintergrund, vor dem sich die im vorliegenden Band versammelten Beiträge mit den Vorstellungen von Staat und Gemeinschaft im George-Kreis beschäftigen. Den Anhängern des Dichters ging es darum, einer prekären Gegenwart das Ideal des 'schönen Lebens' gegenüberzustellen: als Heilmittel gegen Ordnungsverlust, gesellschaftliche Konflikte und innere Zerrissenheit. Die im George-Kreis entwickelten Gemeinschaftsvorstellungen zielten darauf ab, ausgewählten Mitgliedern die Möglichkeit zu geben, ihr ganzheitliches Menschsein zu entwickeln und ihre ästhetischen und intellektuellen Potentiale unter der Führung eines Meisters, Stefan Georges, zu entfalten. Die Frage, ob darüber hinaus durch das Modell einer solchen Gemeinschaft die Gesellschaft als Ganze verändert und ein "Neues Reich" geschaffen werden könnte, entstand bei einzelnen Mitgliedern des Kreises schon vor dem Ersten Weltkrieg, blieb jedoch heftig umstritten. Die Beiträge des Bandes analysieren auch, auf welche Weise sich die Vorstellungen von Staat und Gemeinschaft im Denken, in der literarischen und wissenschaftlichen Produktion sowie den Lebensentwürfen der Kreismitglieder manifestierten. Im Rahmen des George-Kreises wurde das Idealbild einer guten Ordnung nicht im Bereich des Utopischen belassen, sondern in der Lebens- und Forschungspraxis der Kreismitglieder zu verwirklichen versucht.

Wissen und Visionen. Theorie und Politik der Ökonomen im Stefan Georg-Kreis - Schönhärl, Korinna
Der symbolistische Dichter Stefan George sammelte nach der Jahrhundertwende einen Kreis von Dichtern und Intellektuellen um sich, mit denen er arbeitete und lebte, und die er in ihrer wissenschaftlichen Tätigkeit unterstützte. Es überrascht zunächst, dass neben Literaturwissenschaftlern wie Friedrich Gundolf und Historikern wie Ernst Kantorowicz auch einige Wirtschaftswissenschaftler zu diesem "Staat" gehörten. Denn George, der alle Lebensbereiche dem der Kunst untergeordnet sehen wollte, stand dem modernen Kapitalismus sehr kritisch gegenüber und interessierte sich nicht für ökonomische Fragen. Warum übte der Dichter auf die Ökonomen dennoch eine so große Faszination aus, und wieso empfanden sie das Zusammensein mit ihm als Bereicherung für ihre wissenschaftliche Tätigkeit? Edgar Salin, Julius Landmann, Arthur Salz und Kurt Singer vertraten in praktischen wirtschaftspolitischen Fragen sehr unterschiedliche Standpunkte: hier reichte das Spektrum von gemeinwirtschaftlichen bis hin zu liberalen Positionen. In methodologischer Hinsicht dagegen profitierten sie alle von den gestalttheoretischen Ansätzen des George-Kreises, wie sie z.B. Edith Landmann ausarbeitete. Salin etwa entwickelte auf dieser Basis seine "Anschauliche Theorie" für die Volkswirtschaftslehre, die in einer Phase der methodologischen Verunsicherung des Faches nach dem Ende der Historischen Schule Orientierung bieten sollte

„Die Transcendenz des Erkennens“. Erkenntnistheoretische Grundlagen der ökonomischen Methodendiskussion im George-Kreis - Schönhärl, Korinna (Archiv für Kulturgeschichte)

Die Nationalökonomen im George-Kreis und ihre Vorstellungen von Wirtschaft und Staat - Schönhärl, Korinna (Das Ideal des schönen Lebens und die Wirklichkeit der Weimarer Republik)

„In wen der gleiche Funke schlug…“. Wissen und Visionen. Theorie und Politik der Ökonomen im Stefan George-Kreis 1918-1933 - Schönhärl, Korinna (Forschung Frankfurt)

Die Ökonomen des George-Kreises zwischen Historischer Methode und Ökonometrie 1918-1933. Der Ökonom Kurt Singer und die Methode der Semiotik - Schönhärl, Korinna (Auskunft. Zeitschrift für Bibliothek, Archiv und Information in Norddeutschland)

Nachruf auf Clotilde Schlayer - Schönhärl, Korinna (George-Jahrbuch)